NATURAL ALTERNATIVES TO GROWTH-PROMOTING ANTIBIOTICS (GPA) IN ANIMAL PRODUCTION - R. I. Castillo-López; E. P. Gutiérrez-Grijalva; N. Leyva-López; L. X. López-Martínez; J. B. Heredia1 (Journal of Animal and Plant Sciences, 2017)
There is a worldwide tendency to produce the best meat regardless of their origin (i.e., poultry, goats, cows, and pigs) free of drug residues, bacteria causing food toxicity, and contaminants (chemicals), ensuring consumers high-quality products. These pollutants are used in animal feed to improve the characteristics of raw materials, fodders, and/or animal products, to prevent diseases, and to increase production. The most commonly used additives are antibiotics or antimicrobial agents used as growth promoters (GPA) whose global trend is to avoid their use due to the risk of developing bacterial resistance, and vertical and horizontal transmission that can impact on human health, on animal wellness, and on productivity. Therefore, the search for new plant origin alternatives to replace the GPA's such as herbs, spices, plant extracts and/or essential oils to be used as antimicrobials and to also make them available to contribute to animal nutrition.
Keywords: antibiotic (antimicrobial) growth promoters; additives; plant extracts; essential oils